2014
DOI: 10.1111/1365-2435.12293
|View full text |Cite
|
Sign up to set email alerts
|

Natural enemy ecology: comparing the effects of predation risk, infection risk and disease on host behaviour

Abstract: Summary1. Growing interest in unifying the field of natural enemy ecology has revealed similarities between predation and parasitism. In parallel with predation, parasite infection -and even the threat of infection -can alter host traits and indirectly affect community interactions. Nonetheless, few studies have considered multiple mechanisms of natural enemy-induced behavioural alteration in parallel (e.g. effects before and after enemy contact) or the factors that drive variation in behavioural responses. 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 69 publications
(85 reference statements)
1
28
1
Order By: Relevance
“…Most studies of such effects have focused on predators rather than parasites, perhaps because parasites are less likely to directly cause mortality (Combes, 2001). Yet indirect effects of both forces are also possible, whereby 'fear' of predators reduces fitness (Clinchy et al, 2013) and infection by parasites alters behaviour, reduces fecundity or mating success (Raffel et al, 2008;Preston et al, 2014). Recognizing the existence of such effects, and the fact that parasites tend to be much more abundant than predators, it remains uncertain which class of enemy has a stronger effect on the evolution of natural populations, especially on behavioural traits (Kortet et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of such effects have focused on predators rather than parasites, perhaps because parasites are less likely to directly cause mortality (Combes, 2001). Yet indirect effects of both forces are also possible, whereby 'fear' of predators reduces fitness (Clinchy et al, 2013) and infection by parasites alters behaviour, reduces fecundity or mating success (Raffel et al, 2008;Preston et al, 2014). Recognizing the existence of such effects, and the fact that parasites tend to be much more abundant than predators, it remains uncertain which class of enemy has a stronger effect on the evolution of natural populations, especially on behavioural traits (Kortet et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Second, host behavioural traits and responses to infection may contribute. Because parasites such as R. ondatrae cause considerable damage to the host tissue during encystment, often leading individuals with heavy infections to exhibit reduced activity 12–48 hr following exposure, shifts in host behavioural responses (including reduced avoidance behaviour) could enhance transmission in a nonlinear manner—particularly if it generated among‐host variation (Johnson & Hoverman, ; Preston, Boland, Hoverman, & Johnson, ). Other studies have reported that variation in host size or developmental stage can also influence parasite aggregation (Holland et al., ), although we endeavoured to keep these traits as constant as possible within our manipulations.…”
Section: Discussionmentioning
confidence: 99%
“…We tested the interplay between biotic and abiotic constraints on amphibian response to climate change, as these animals are sensitive to environmental stress and have long been used to investigate antagonistic interactions, particularly competition, predation, and parasite/pathogen dynamics (e.g., Peacor and Werner , Preston et al. , Youngquist et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…This complex interplay requires evaluation of how changing environmental conditions affect the strength and direction of multi-species interactions (e.g., Hoover et al 2012, Milazzo et al 2013, Rysavy et al 2016) and, potentially, how interactions can mediate the impact of environmental stress (e.g., McGuire and Agrawal 2005, Suttle et al 2007, Alexander et al 2015. We tested the interplay between biotic and abiotic constraints on amphibian response to climate change, as these animals are sensitive to environmental stress and have long been used to investigate antagonistic interactions, particularly competition, predation, and parasite/pathogen dynamics (e.g., Peacor and Werner 1997, Preston et al 2014, Youngquist et al 2015. While pairwise assessments of species interactions under different environmental conditions are quite valuable (see Rogers andChalcraft 2008, Vogel andPechmann 2010; for further review of amphibian experiments see Appendix S1: Tables S1 and S2), we posit the need for research investigating the combined effects of multiple interacting amphibian species and environmental stress.…”
Section: Introductionmentioning
confidence: 99%